2008
DOI: 10.1128/jb.00785-08
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Pathogenicity Island PAGI-5 Contributes to the Highly Virulent Phenotype of a Pseudomonas aeruginosa Isolate in Mammals

Abstract: Most known virulence determinants of Pseudomonas aeruginosa are remarkably conserved in this bacterium's core genome, yet individual strains differ significantly in virulence. One explanation for this discrepancy is that pathogenicity islands, regions of DNA found in some strains but not in others, contribute to the overall virulence of P. aeruginosa. Here we employed a strategy in which the virulence of a panel of P. aeruginosa isolates was tested in mouse and plant models of disease, and a highly virulent is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
101
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 61 publications
(71 reference statements)
3
101
0
3
Order By: Relevance
“…Among a panel of 35 P. aeruginosa isolates cultured from patients with ventilator-associated pneumonia, these cargo regions were present in only the more virulent strains ( Fig. 3) (14). Additional studies confirmed that these regions of PAGI-5 contribute to pathogenicity, as deletion of either attenuated virulence in a mouse model of acute pneumonia (14).…”
Section: Icesmentioning
confidence: 50%
See 1 more Smart Citation
“…Among a panel of 35 P. aeruginosa isolates cultured from patients with ventilator-associated pneumonia, these cargo regions were present in only the more virulent strains ( Fig. 3) (14). Additional studies confirmed that these regions of PAGI-5 contribute to pathogenicity, as deletion of either attenuated virulence in a mouse model of acute pneumonia (14).…”
Section: Icesmentioning
confidence: 50%
“…2). Illustrating the capacity of ICEs to continually evolve through acquisition and loss of cargo ORFs, PAGI-5 carries two regions of cargo ORFs (NR-I and NR-II) that are absent in PAPI-1 (14). Among a panel of 35 P. aeruginosa isolates cultured from patients with ventilator-associated pneumonia, these cargo regions were present in only the more virulent strains ( Fig.…”
Section: Icesmentioning
confidence: 99%
“…Vários grupos de genes de PAPI-1 também estão presentes nos plasmídeos pKLC102 e pKLK106, e nas ilhas genômicas PAGI-2, PAGI-3 e PAGI-5 (Larbig, et al 2002;Battle, et al 2008). As regiões variantes em PAGI-2, -3 -5 parecem conferir capacidades diferentes de adaptação para estas linhagens, assim como as regiões variantes de PAPI-1 se mostraram relevantes em patogenicidade (Kiewitz, et al 2000;Klockgether, et al 2004;Battle, et al 2008).…”
Section: Ilhas Na Linhagem Pa14unclassified
“…As regiões variantes em PAGI-2, -3 -5 parecem conferir capacidades diferentes de adaptação para estas linhagens, assim como as regiões variantes de PAPI-1 se mostraram relevantes em patogenicidade (Kiewitz, et al 2000;Klockgether, et al 2004;Battle, et al 2008). Recentemente, ilhas semelhantes a PAGI-2 foram detectadas em 31 de um total de 71 linhagens de P. aeruginosa analisadas e também na -proteobactéria Cupriavidus (Ralstonia) metallidurans (Klockgether, et al 2007).…”
Section: Ilhas Na Linhagem Pa14unclassified
See 1 more Smart Citation